 Topics in

P R E C A L C U L U S

23

# FACTORIALS

BY THE SYMBOL n! ("n factorial") we mean the product of consecutive numbers 1 through n.

 n! = 1· 2· 3·  ·  · (n − 2)(n − 1)n = n(n − 1)(n − 2)·  ·  · 3· 2· 1

The order of the factors does not matter, whether backwards or forwards.

0! is defined as 1.

0! = 1.

(The usefulness of this definition will become clear as we continue.)

Example.   6! = 1· 2· 3· 4· 5· 6 = 720

A convenient way to calculate this is to wait to multiply 2· 5 = 10.  Then

3· 4· 6 = 12· 6 = 72

-- times 10 is 720.

Calculations with factorials are based on this fact:

Any factorial less than n! is a factor of n!.

Example 1.   6! is a factor of 10!.  For,

 10! = 1· 2· 3· 4· 5· 6· 7· 8· 9· 10 = 6!· 7· 8· 9· 10
 Example 2.   Evaluate 8!5! .
 8!5! = 1· 2· 3· 4· 5· 6· 7· 8       1· 2· 3· 4· 5 = 6· 7· 8 = 6· 56 = 336
 Example 3.   Evaluate 8!  6! 2! .

Solution.  6! is a factor of 8!, so it will cancel  leaving 7· 8 in the

 numerator.  We will have 7· 81· 2 = 28.

Problem 1.   What factorial is each of these?  (Consider what each symbol means.)

To see the answer, pass your mouse over the colored area.
To cover the answer again, click "Refresh" ("Reload").

a)  3!· 4  = 4!  For, 3!· 4 = 1· 2· 3· 4 = 4!.         b)  6!· 7· 8  = 8!

c)  (n − 1)! n  = n!              d)  (nk − 1)! (nk) = (nk)!

 Problem 2.   Evaluate 10! 7! .
 10! 7! = 7!· 8· 9· 10      7! = 8· 9· 10 = 720
 Problem 3.   Evaluate 12!   10! 2! .
 12!   10! 2! = 10!· 11· 12   10! 2! = 11· 12  1· 2 = 11· 6 = 66
 Example 4.   Show: 1     (n − 1)! = n n!

Solution.  If we multiply both terms on the left by n, then

 1     (n − 1)! = n      (n − 1)! n

For, (n − 1)! is the product up to the number just before n.  Therefore, (n − 1)! times n itself  is n!.

 1     (n − 1)! = n      (n − 1)! n = n n!

Example 5.   Show:  n! k  +  n! (nk + 1) = (n + 1)!

Solution.   On the left-hand side, n! is a common factor:

 n! k  +  n! (n − k + 1) = n! (k + n − k + 1) = n! (n + 1),   on canceling the k's, = (n + 1)!

For, (n + 1) is the number after n.

Problem 4.   Write out the steps that show how to transform the left-hand side into the right-hand side.  Again, consider what each symbol means.

 a) 13! = 44!

Multiply both terms on the left by 4:

 1 3! = 4  3!· 4 = 44!
 b) 1     (k − 1)! = k k!

Multiply both terms on the left by k:

 1    (k − 1)! = k      (k − 1)!· k = k k!
 c) 12 12! = 1 11!

Since 12! = 11!· 12, divide both terms on the left by 12:

 12 12! = 12   11!· 12 = 1 11!
 d) n − k  (n − k)! = 1        (n − k − 1)!

Since (nk)! = (nk − 1)!· (nk), divide both terms on the left by (nk):

 n − k  (n − k)! = n − k           (n − k − 1)!· (n − k) = 1        (n − k − 1)!

e)   5!· 4  +  5!· 2 = 6!

5! is a common factor:

5!· 4  +  5!· 2 = 5!(4 + 2) = 5!· 6 = 6! Next Topic:  Permutations and combinations

Please make a donation to keep TheMathPage online.
Even \$1 will help.